Influência da população de plantas, doses de nitrogênio e controle de doenças na produção e qualidade de grãos e sementes de arroz irrigado - Marzari, Victor (2005)
The objective of this study was to evaluate the effect of plant densities, nitrogen levels and foliar diseases control on grain yield and seed quality of irrigated rice. An experiment was conducted in Santa Maria RS Brazil, during 2003/2004 growing season aiming to evaluate the effects, plant populations, nitrogen levels and fungicide application on grain yield (Chapter I) and seed quality (Chapter II) of irrigated rice. Were evaluated grain yield and seed quality under three plant densities (150, 265 and 380 plants m-2), five nitrogen levels (0, 40, 80, 120 and 160 kg ha-1) with and without fungicide application. There was no triple interaction among the parameters evaluated. Higher plant populations resulted in fewer tillers per plant and seeds per panicle increasing interspecific competition and grain yield was not significantly affect as result os yield components compesation. Nitrogen increased seed yield up to 97 kg ha-1 wich was not affected by plant population and an hanced the nutritional quality as result of increased protein content. Diseases control had a positive effect on grain yield and quality as well as of the rice seeds by reducing its incidence and increased germination percentage.